Understanding empowerment for a healthy dietary intake during pregnancy - Sabina Super; Annemarie Wagemakers (International Journal of Qualitative Studies on Health & Well-Being, 2021)
Purpose: In order for health professionals to encourage pregnant women with a low socioeconomic status (SES) to move towards empowerment for a healthy dietary intake, crucial steps are to understand the perspectives of pregnant women of food and eating and to identify opportunities for empowerment. This study aimed to examine the perspectives of pregnant women on food and eating and to identify the opportunities for empowerment towards a healthy dietary intake. Methods: This was a qualitative participatory study. Thirteen semi-structured interviews were conducted with low SES pregnant women in the Netherlands and analysed using an inductive approach. Results: Five perspectives on food and eating emerged: 1) health-promoting foods and products, 2) challenges in healthy eating, 3) risky products, 4) strategies for healthy eating, and 5) motivational aspects. Opportunities for empowerment were: searching balanced and personalized information, developing strategies to implement healthy diets, navigating the social environment, and dealing with different motivations. Conclusion: Pregnant women hold diverse perspectives regarding food and eating, signalling the need to adjust dietary support from health-care professionals. Professionals in antenatal care could optimize their interactions by engaging in pregnant women’s empowerment processes to make healthy modifications to their dietary intake.